The 'Civil Society Policy' of the European union for promoting democracy in Turkey: Golden goose or dead duck? - Zihnioğlu, Özge (Routledge Journals, Taylor & Francis Ltd, 4 Park Square, Milton Park, Abingdon Ox14 4Rn, Oxfordshire, England, 2013)
Golden goose' of European integration for some time now, EU's civil society policy displays a vivid example during Turkey's accession. This article queries the impact of this policy in the Turkish context, ultimately showing its limited extent on Turkish civil society organizations (CSOs) and illuminating its real constraints in the Turkish context. Drawing on interviews with CSOs, this article argues that the EU could not accomplish its expected objectives set within its civil society policy in Turkey due to its neo-Tocquevillian conceptualization that overlooks at the constraints on civil society actors and disregards civil society's political nature and its CSOs' autonomous character.
Keywords: Turkey; Civil Society; European Union; Democratization; Neo-Tocquevillian; Türkiye; Sivil Toplum; Avrupa Birliği; Demokratikleşme